2015
DOI: 10.1007/s12035-015-9333-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuroprotection of Acetyl-11-Keto-β-Boswellic Acid (AKBA)-Loaded O-Carboxymethyl Chitosan Nanoparticles Through Antioxidant and Anti-Inflammatory Pathways

Abstract: Acetyl-11-keto-β-boswellic acid (AKBA), a main active constituent from Boswellia serrata resin, is a novel candidate for therapy of cerebral ischemia-reperfusion (I/R) injury. Nevertheless, its poor solubility in aqueous solvent, bioavailability, and rapid clearance limit its curative efficacy. To enhance its potency, in our study, AKBA-loaded o-carboxymethyl chitosan nanoparticle (AKBA-NP) delivery system was synthesized. The transmission electron microscopy and transmission electron microscope images of AKBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…In addition, oxygen plasma treatment preserves the chitosan microstructure in nerve conduit models, confirming improvement in behavior and functional recovery (Cheng et al, 2007). Chitosan nanoparticles loaded with acetyl-11-keto-β-boswellic acid, a resin extract which may control inflammatory responses, demonstrate a neuroprotective effect in a MCAO rat model, reducing infarct volume and cell death (Ding et al, 2016). In addition, the encapsulation of ESC derived ECs into a chitosan-based hydrogel loaded with VEGF microtubes presents minimal cytotoxicity in vivo and high cell survival, inducing neovascularization in hind limb ischemia mouse models (Lee et al, 2015).…”
Section: Chitosanmentioning
confidence: 72%
“…In addition, oxygen plasma treatment preserves the chitosan microstructure in nerve conduit models, confirming improvement in behavior and functional recovery (Cheng et al, 2007). Chitosan nanoparticles loaded with acetyl-11-keto-β-boswellic acid, a resin extract which may control inflammatory responses, demonstrate a neuroprotective effect in a MCAO rat model, reducing infarct volume and cell death (Ding et al, 2016). In addition, the encapsulation of ESC derived ECs into a chitosan-based hydrogel loaded with VEGF microtubes presents minimal cytotoxicity in vivo and high cell survival, inducing neovascularization in hind limb ischemia mouse models (Lee et al, 2015).…”
Section: Chitosanmentioning
confidence: 72%
“…Recently, Ding et al . () showed that nanoformulation of AKBA leads to enhanced protection of AKBA against cerebral ischemic insult by improving antioxidant defence (SOD and glutathione peroxidase) and diminishing inflammation (TNF‐α and IL‐1β), as well as the improvement activation of the nuclear factor erythroid‐2‐related factor 2/heme oxygenase‐1 pathway and inhibition of inflammatory protein expressions (NF‐kB and 5‐lipoxygenase). Sayed and El Sayed () showed that co‐administration of AKBA and celecoxib reversed the behavioural and molecular changes caused by lipopolysaccharide‐induced cognitive dysfunction in mice.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study also revealed that beta-boswellic acid could significantly enhance neurite outgrowth and branching of primary cells of hippocampal tissue in rats (Karima et al, 2010). Recently, Ding et al (2016) showed that nanoformulation of AKBA leads to enhanced protection of AKBA against cerebral ischemic 1964 F. FOROUZANFAR ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Trapezoidal rule was used for the estimation of the area under plasma concentration time. 48 further studied anti-inflammatory activity in the form of herbal gel for management of gout. The physicochemical properties of drug were evaluated on the basis of solubility, UV, FTIR, HPLC and DSC.…”
Section: Advantages Of Hplcmentioning
confidence: 99%